2017
DOI: 10.3390/s17081923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flexible Force Sensors for Pressure Monitoring in Treatment of Chronic Venous Disorders

Abstract: The recent use of graduated compression therapy for treatment of chronic venous disorders such as leg ulcers and oedema has led to considerable research interest in flexible and low-cost force sensors. Properly applied low pressure during compression therapy can substantially improve the treatment of chronic venous disorders. However, achievement of the recommended low pressure levels and its accurate determination in real-life conditions is still a challenge. Several thin and flexible force sensors, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…This study was performed using two low-cost commercially available thin and flexible piezoresistive force sensors: the Peratech quantum tunnelling composite (QTC) TM SP 200-10 sensor and the Sensitronics ® Half Inch ThruMode FSR ( Figure 1 ). These sensors were selected on the basis of a previous study [ 25 ] that determined the most suitable and the best-performing of five pressure sensors suitable for compression therapy applications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed using two low-cost commercially available thin and flexible piezoresistive force sensors: the Peratech quantum tunnelling composite (QTC) TM SP 200-10 sensor and the Sensitronics ® Half Inch ThruMode FSR ( Figure 1 ). These sensors were selected on the basis of a previous study [ 25 ] that determined the most suitable and the best-performing of five pressure sensors suitable for compression therapy applications.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated the effect of changes in underlying surfaces on the pressure sensing performance of two commercially available sensors on a human-leg-like test setup that is representative of human soft tissue surfaces. The sensors were selected from a wide range of commercial sensors based on our previous research [ 25 ], which demonstrated that they were the most suitable for compression therapy. The pressure measurements were conducted in a low pressure range (20–70 mmHg) appropriate for compression therapy treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Marco et al [5] performed the sensor calibrations using robotic platform that can precisely apply controllable loads to the desired positions. Parmar et al [37] evaluated the performance of 5 different commercial FSRs during static and dynamic loading with reliable test setups that can mimic realistic conditions when applying pressure on human limbs. The sensors were evaluated quantitatively based on their accuracy, drift, and repeatability behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To calculate the sensitivity of the sensor, the estimated force values on the test experiments are considered over all folds. Flexible piezoresistive sensors often have a lower accuracy and high level of noise within the low range of the applied force [49]. Therefore, all the data points with the force value of less than 0.2 N are eliminated for the purpose of sensitivity calculation.…”
Section: Force Estimationmentioning
confidence: 99%